Determinants of Individual Investor Behavior in Nepalese Stock Market - Adhikari, Upasana; Pradhan, Radhe Shyam (Nepalese Journal of Economics, 2024)
This study examines the determinants of individual investor behavior in Nepalese stock market. The dependent variable of the study is individual investment behavior. Similarly, the selected independent variables are investment opportunities, purpose of investment, sources of information, sources of influence, herding and financial instruments. The primary source of data is used to assess the opinions of the respondents regarding investment opportunities, purpose of investment, sources of information, sources of influence, herding and financial instruments in Nepalese stock market. The study is based on primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors on individual investor behavior in Nepalese stock market. The study showed that financial instruments and purpose of investment have a positive impact on individual investment behavior. It implies that availability of better financial instruments drives the individual investment behavior. Likewise, multiple purpose of investment leads to increase in individual investment behavior. Moreover, investment opportunity has a positive impact on individual investment behavior indicating that increase in suitable investment opportunities lead to increase in individual investment behavior. Furthermore, source of information has a positive impact on individual investment behavior. It implies that the reliable source of information leads to increase in individual investment behavior. Similarly, the result also revealed that sources of influence have a positive impact on individual investment behavior indicating that proper influential factor in the market leads to increase in individual investment behavior. In addition, herding has a positive impact on individual investment behavior. It reveals that herding factor stimulates the individual investment behavior.